2015
DOI: 10.1111/idh.12125
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine mouthwash and sodium lauryl sulphate dentifrice: do they mix effectively or interfere?

Abstract: This review demonstrates that when CHX mouthwash is recommended, it can be used in combination with an SLS dentifrice without any interference regarding its inhibiting effect on dental plaque, regardless of the order of use. Consequently, the collective evidence indicates that the combined use of dentifrice and CHX mouthwash is not contraindicated. However, this recommendation has been graded as moderate taking into account a potential publication bias because three of the four included studies emerged from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This is in contrast to the findings of a systematic review that showed that the combination of CHX and a SLS dentifrice is not contraindicated. 39 Therefore, the regular dentifrice in the pre‐experimental phase could be used without any specific instruction regarding CHX effectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the findings of a systematic review that showed that the combination of CHX and a SLS dentifrice is not contraindicated. 39 Therefore, the regular dentifrice in the pre‐experimental phase could be used without any specific instruction regarding CHX effectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential effect of SLS from dentifrice slurry on CHX efficacy was evaluated. Based on the collective evidence, it was concluded that under normal brushing circumstances, an SLS dentifrice could be used without any interference with CHX activity regarding its inhibiting effect on the dental plaque …”
Section: Discussionmentioning
confidence: 99%
“…[ 7 8 ] The set of instructions given to the subjects in Group A to use it half an hour after brushing was due to the cationic nature of the compound which tends to interact with the anionic detergent in the tooth paste and thus is not effective if used immediately. [ 26 ] Furthermore, they were told to refrain from eating and drinking for 20 min after its use which was to avoid staining of the teeth as CHX reacts with colored components in food items. Subjects who were working/college students found it difficult to follow these instructions in the morning when they had limited time and thus, they presented with staining.…”
Section: Discussionmentioning
confidence: 99%